2016
DOI: 10.1111/1748-8583.12113
|View full text |Cite
|
Sign up to set email alerts
|

A mutual gains perspective on workplace partnership: Employee outcomes and the mediating role of the employment relations climate

Abstract: Recent years have witnessed increased research on the role of workplace partnership in promoting positive employment relations. However, there has been little quantitative analysis of the partnership experiences of employees. This paper examines how the kinds of attributions employees make regarding indirect (union-based) and direct (non-union-based) employee participation in workplace partnership might influence the process of mutual gains. It uses employee outcomes to reflect partnership gains for all stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…Thus, our work has a number of theoretical implications. First, this finding is noteworthy because partnership theory has for the most part focused on the conditions necessary for positive and sustainable trade union (e.g., Ackers & Payne, : Terry, ) and employee (e.g., Glover et al, ; Valizade et al, ) outcomes. Even though standard formulations cite the reconciliation of employee and employer interests through dialogue (Belanger & Edwards, ), the factors driving a successful managerial agenda have received far less comment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our work has a number of theoretical implications. First, this finding is noteworthy because partnership theory has for the most part focused on the conditions necessary for positive and sustainable trade union (e.g., Ackers & Payne, : Terry, ) and employee (e.g., Glover et al, ; Valizade et al, ) outcomes. Even though standard formulations cite the reconciliation of employee and employer interests through dialogue (Belanger & Edwards, ), the factors driving a successful managerial agenda have received far less comment.…”
Section: Discussionmentioning
confidence: 99%
“…This speaks to both industrial relations analyses of workplace partnership and the leadership/change literature more broadly. Although the former body of work has identified several of the antecedents of successful partnership arrangements (e.g., Butler et al, : Oxenbridge & Brown, ; Valizade et al, ), the phenomenon of distributed leadership has not hitherto figured in such modelling. Similarly, the leadership literature is still in need of research inquiring into the environmental and organisational factors favourable to the continuity of novel leadership configurations (e.g., Gronn, , p. 445).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to test the criterion‐related validity of the scale, we examined the intercorrelation between the HR attributions subscales and constructs found to correlate with the attributions from prior research, organizational citizenship behavior (OCB), job satisfaction, and intention to quit (Nishii et al, ; Valizade, Ogbonnaya, Tregaskis, & Forde, ). In line with prior research, we found that commitment‐focused HR attributions were positively correlated with OCB ( r = .27, p < .01), and job satisfaction ( r = .45, p < .01), and negatively related to intention to quit ( r = −.36, p < .01).…”
Section: Empirical Studymentioning
confidence: 99%
“…This is surprising given that one key aim of an industrial relations system is the fostering of economic productivity in organizations (Dunlop, ). The present study therefore asks whether employees' perceptions of the industrial relations climate, defined as the extent to which employees perceive the relationship between the management and the union as being cooperative (Deery, Iverson, Buttigieg, & Zatzick, ), and union instrumentality, defined as the extent to which employees believe the union is effective in acting in their interests (Valizade, Ogbonnaya, Tregaskis, & Forde, ), influence their job performance, and the underlying mechanisms, which explain such effects. We examine these issues in the context of the Chinese private sector, which has grown rapidly during the last 40 years of opening up and reform and now accounts for the lion's share of employment in China (Atherton & Newman, ).…”
Section: Introductionmentioning
confidence: 99%